Constructing bilingual input safe spaces at home: rethinking exposure to language from a multilingual and multisite perspective on literacy practices - Costa Wätzold, Juliane; Melo-Pfeifer, Sílvia (Frontiers in Language Sciences, 2024)
Drawing from interviews with parents and focus groups with children (aged 4-14), this article analyses parents' and children's attitudes towards the different literacy practices across three different contexts (at home, in a community project, and, indirectly, at school) and how they perceive the interaction between these practices and the development of competences in the heritage language (HL). We investigate the relevance of family and community, and how mainstream school influences the coconstruction of literacy practices that affect the development of HL, while at the same time supporting the development of the majority language, and especially in broadening the understanding of the notion of language exposure. We make the case that exposure to literacy practices in the majority language is interpreted and (re)appropriated by families and communities to support the development of complex and integrated literacy practices involving the different languages of children's repertoires. We shed light on how families construct bilingual input safe spaces at home, i.e., spaces where continuities between formal, informal and non-formal literacy practices in both German and Portuguese are assured. The results bring a critical perspective on the ecology of literacy practices and highlight the added value of seeing literacy practices interconnected holistically from a co-developmental viewpoint, with a positive impact not only in children's HL but also in the majority language, and potentially in the languages learnt at school.